Throughout Your Generations Forever Sacrifice, religion and paternity - Jay, Nancy; Fields, Karen E. (Chicago, London : The University of Chicago Press, 1992)
1. Social-Scientific Interpretation of Ritual
2. The Logic of Sacrifice
3. Sacrifice and Descent
4. Creating Descent through Fathers and Sons
5. Ashanti Sacrifice
6. Hawaiian Sacrifice
7. Sacrifice, Descent and the Patriarchs
8. Sacrifice and Social Structure in Christianity
9. Theories of Sacrifice
Appendix : Sacrificial Calendars
bibliogr.